Effect of Controlled Grazing on Vegetation Cover of Sewan (Lasiurus SindiclJs Henr.) Rangeland in Arid Western Rajasthan - Bawa, A K (Annals of Arid Zone, 2016)
Studies revealed that controlled grazing of the Sewan rangeland did not adversely affect primary productivity and the dominant forage grass i.e. Sewan (Lasillrus sindicuS) continued to dominate in terms of significantly higher frequency, cover and forage yield over associated species.